Spectroscopic study on peculiarities of fumed silica hydridesilylation with triethoxysilane under fluidized bed conditions - Kuzema, P. O.; Korobeinyk, A. V.; Tertykh, V. A. (Chemistry, Physics & Technology of Surface / Khimiya, Fizyka ta Tekhnologiya Poverhni, 2021)
Fumed silica has found widespread application in industry due to variety of fascinating properties. Owing to its specific manufacturing process, it consists of finely dispersed particles and is featured with large specific surface area covered by profoundly reactive silanol groups which are available for chemical grafting. Spherical shape of fumed silica particles and lacking porosity provides a space-filling structure. These characteristics implement the fume silica’s utilization as high-surface-area carriers for various catalysts, i.e. metallic nanometer-sized particles, organic moieties, etc. Currently a great attention is called to on-surface grafting to improve the silica-based carrier. Most of research is carried out in area of liquid phase chemistry involving an abundance of expensive and often toxic solvents while the space-filling properties of silica are favoring reactions in fluidized bed conditions. In current research fumed silica (A-300) was a subject for hydridesilylation with triethoxysilane under fluidized bed conditions. In all synthesis reported in current research the insignificant amount of solvent (1.00 wt. % of the amount used in typical wet-chemical modifications method) was spent for the silica surface silylation. While the mass ratio of silica/TES was kept constant, other conditions, i.e. solvent/catalyst presence, surface pretreatment, additional treatment with water, and the fluidized bed heating mode have been varied. FTIR spectroscopy revealed the interaction between groups of triethoxysilane and silica surface silanol groups and demonstrated the effect of modification conditions on the density of the hydridesilyl groups coverage. The results of FTIR spectroscopic studies have confirmed the presence of grafted silicon hydride groups on the surface of modified silica, as well as the presence of ethoxy and/or silanol groups – either intact or formed due to hydrolysis of the ethoxy groups. Titrimetric and spectrophotometric analysis was performed to estimate the concentration of grafted SiH groups (in all samples prepared under fluidized bed conditions their concentration ranged within about 0.28–0.55 mmol/g as dependent on the reaction conditions). Other important aspects of fluidization such as the presence of solvent and/or hydrolyzing agent, bed heating mode and the effect of the silica sample thermal pre-treatment are also discussed.